A Transition Metal‐Free Approach for the Conversion of Real‐Life Cellulose‐Based Biomass into Formate - Tong Zhang; Peng Ren; Yuman Qin; Thanh Huyen Vuong; Ana V. Cunha; Remco W. A. Havenith; Jabor Rabeah; Shoubhik Das (Advanced Science)
Abstract Formic acid (FA) and its salt are recognized as valuable molecules for various industries such as textiles and pharmaceuticals. Currently, the global demand of FA and its salts stands at 1.137 million metric tons per year, necessitating the development of sustainable methods to meet the future demands. While numerous approaches are developed for the generation of FA but the requirement of harsh reaction conditions to achieve them is unavoidable. On the other hand, the world production of biomass is estimated at 146 billion metric tons per year and that can be considered as a prospective source of FA and their salts. Additionally, cellulose accounts for approximately 35–45% of the biomass composition. Considering this, a visible‐light‐mediated approach is presented to produce formate directly from biomass at room temperature as well as at atmospheric pressure. In this approach, selective generation of hydroxyl radical has been achieved which later converted sugars, cellulose, and hemicellulose into formate. Furthermore, the conversion of cellulose‐rich daily‐life materials such as discarded paper into the product through a series of flow experiments is demonstrated. Finally, mechanistic investigations including electron paramagnetic resonance (EPR) spectroscopy, and density functional theory (DFT) calculations are conducted to gain insights into the underlying reaction mechanism.